2022
DOI: 10.3390/foods11030450
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Food-Grade Pickering Emulsions Stabilized with Chitosan-Phytic Acid-Cyclodextrin Nanoparticles

Abstract: This study aimed to fabricate food-grade Pickering emulsions stabilized by chitosan-phytic acid-β-cyclodextrin (CS-PA-CD) nanoparticles. The CS-PA-CD nanoparticles were characterized with FITR, XRD, and TGA to prove its successfully crosslinking, then characterized by DLS system and scanning electron microscopy showing the smallest average particle size was 434.2 ± 2.5 nm and it increased with the ratio of PA-CD to CS increasing. Pickering emulsions stabilized by CS-PA-CD nanoparticles was prepared and it show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Notably, when TPOR is combined with DOX, there is a significant enhancement in SOSG fluorescence prior to binding. Previous studies have reported that DOX sensitizes photosensitizer-mediated photodynamic therapy [ 45 , 46 ]. Consequently, DOX promotes the production of 1 O 2 when used in conjunction with TPOR.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, when TPOR is combined with DOX, there is a significant enhancement in SOSG fluorescence prior to binding. Previous studies have reported that DOX sensitizes photosensitizer-mediated photodynamic therapy [ 45 , 46 ]. Consequently, DOX promotes the production of 1 O 2 when used in conjunction with TPOR.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic oligosaccharide beta-cyclodextrin (β-CD) is obtained from the controlled enzymatic hydrolysis of starch and is formed by seven D-glucopyranose units linked by 1,4-glucosidic bonds [ 27 , 28 ]. β-cyclodextrin (β-CD) with a hydrophobic cavity interior and hydrophilic cavity exterior structure acts as a very good Pickering emulsifier at room temperature due to both the solubility in water and the capability of the encapsulation of the hydrophobic ingredients [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beta-cyclodextrin (β-CD) is a cyclic oligosaccharide consisting of seven d -glucopyranose units connected by 1,4-glucosidic bonds [ 16 18 ]. β-CDs have a central hydrophobic cavity and outer hydrophilic surface, enabling them to encapsulate lipophilic drugs [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%